Fertility rebound and economic growth. New evidence for 18 countries over the period 1970-2011 - Piotr Dominiak,; Ewa Lechman; Piotr Anna Okonowicz (Institute of Economic Research (IER), 2014)
Long-run impact of economic growth on fertility trends is ambiguous and sensitive for in-time variations. Noticeably, over last decades, economic growth has led in many countries to significant falls in total fertility rates. However, recently, in high-income economies a kind of 'fertility rebound' emerged (Goldstein, 2009; Luci and Thevenon, 2011; Day, 2012), which supports the hypothesis that reversal trends in total fertility rates are mainly attributed to economic growth. The paper unveils the relationship between total fertility rate changes and economic growth in 18 selected countries with fertility rebound observed, over the period 1970-2011, and detects the GDP-threshold at which the fertility rebound emerged. To report on the relationship we deploy longitudinal data analysis assuming non-linearity between examined variables. Data applied are exclusive derived from World Development Indicators 2013. Our main findings support the hypothesis on U-shaped relationship between total fertility rate and economic growth in analyzed countries in 1970-2011. Along with the previous we project the minimum level of GDP per capita (GDP-threshold) when the fertility rebound takes place.
Keywords: J11; O10; C23; 330; fertility rate; fertility rebound; economic growth; panel data analysis